Effect of exogenous microflora of the hepatobiliary system on the biochemical composition of bile and lipid peroxidation processes of somatic cell membranes in chronic opisthorchiasis - N. M. Fedorov; A. G. Rybka; P. B. Zotov (Сибирский научный медицинский журнал, 2021)
It has been epidemiologically established that the rate of primary cholangiocarcinomas increases greatly in the ObIrtysh basin which is hyperendemic for helminth Opisthorchis felineus in comparison with other regions where the population is not infested. In this connection chronic opisthorchiasis is considered as facultative liver precancer. The study of cholangiocarcinogenesis mechanisms will allow developing pathogenetic approaches to prevention of this tumor. Aim of the study was to investigate the significance of microbiota of the hepatobiliary tract of chronic opisthorchiasis patients in changing of biochemical composition of bile and investigation of its biological influence on somatic cells membrane. Material and methods. Objects of research: bacteria; inbred mice infected by opisthorchis; samples of bile, cultures of human embryo fibroblasts and splenocytes of inbred mice in vitro; blood plasma; standard primary and secondary bile acids. We studied: species of bacteria colonizing bile ducts; quantitative and qualitative composition of bile acids, and level of diene conjugates and malondialdehyde in duct bile samples; biological activity of bile on processes of lipid peroxidation of cell membranes in vitro; influence of bile and lipid peroxidation products on cytomembrane permeability; activity of antioxidant systems of the body. Results and discussion. It was found out, that bile of patients with chronic opisthorchiasis in majority of cases (77.0 %) was infected by different species of bacteria. In 30.0 % of cases certain types of intestinal bacteria (Proteus vulgaris, P. mirabilis, Citrobacter freundii, Bacteroides alcaligues faecalis, Clostridium, Streptococcus faecalis, Escherichia coli) change biochemical composition of duct bile – deconjugated primary and secondary bile acids and also high level of total bile acids are detected. Bile of the above biochemical composition, against the background of depletion of antioxidant system, induces activation of cell membrane lipid peroxidation processes and significantly increases their permeability to toxic components of bile. These processes are promotor in cholangiocarcinogenesis.